2013
DOI: 10.1371/journal.pone.0054079
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Cacao Trees in Waslala, Nicaragua: Associations between Genotype Spectra, Product Quality and Yield Potential

Abstract: The sensory quality and the contents of quality-determining chemical compounds in unfermented and fermented cocoa from 100 cacao trees (individual genotypes) representing groups of nine genotype spectra (GG), grown at smallholder plantings in the municipality of Waslala, Nicaragua, were evaluated for two successive harvest periods. Cocoa samples were fermented using a technique mimicking recommended on-farm practices. The sensory cocoa quality was assessed by experienced tasters, and seven major chemical taste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…Specific chocolate flavor notes have been related to cocoa tree variety and growing conditions, postharvest treatments, and the chocolate manufacturing process (4,5). For example, it has been shown that different cocoa tree genotypes influence the flavor of fermented beans and liquor (2,(47)(48)(49)(50). However, modulating chocolate flavor by changing the cocoa cultivar would require elaborate plantation management by planting (a combination of) specific cocoa tree varieties, which in turn might be more disease susceptible or have a lower yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific chocolate flavor notes have been related to cocoa tree variety and growing conditions, postharvest treatments, and the chocolate manufacturing process (4,5). For example, it has been shown that different cocoa tree genotypes influence the flavor of fermented beans and liquor (2,(47)(48)(49)(50). However, modulating chocolate flavor by changing the cocoa cultivar would require elaborate plantation management by planting (a combination of) specific cocoa tree varieties, which in turn might be more disease susceptible or have a lower yield.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and pH were measured in real time in the middle of the fermenting mass using a digital pH meter (pH 3310 SET 2, SenTixH 41; WTW GmbH, Weilheim, Germany). Cocoa bean samples (200 g each) from the fermentations were taken after 0 (fresh cocoa beans, right after opening the pods), 4,24,48,72, and 96 h. The bean samples were cooled to 4°C and analyzed within 1 h. Therefore, a 40-g sample was mixed with 160 ml of 0.1% peptone water in an aseptic stomacher bag. The suspension was powerfully shaken and manually kneaded for 5 min, and a 10-fold serial dilution in 0.1% peptone water was made of the homogeneous cocoa pulp solution.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in dried and unfermented beans, the level of (−)‐epicatechin decreases by about 50% (Giacometti and others ). It has also been suggested that the reduction of the polyphenol content during fermentation can be influenced by genetic peculiarities, such as anatomical features of the beans (Trognitz and others ).…”
Section: Cocoa Flavor Chemistrymentioning
confidence: 99%
“…If the types of certain foods are not specified (i.e., dark chocolate versus milk chocolate), it is possible to over or underestimate true associations with outcomes [25]. In the case of chocolate, there is a wide variety on theobromine concentration among different types of chocolate and the theobromine/caffeine ratio has also been observed to be highly variable, from 1.9 to 10.6 [26]. Because of this limitation, we decided to focus on chocolate intake, data we could access directly from the FFQ.…”
Section: Chocolate and Caffeine Dietary Intakementioning
confidence: 99%